2024
DOI: 10.3389/fnut.2023.1331854
|View full text |Cite
|
Sign up to set email alerts
|

Athletes’ nutritional demands: a narrative review of nutritional requirements

Adam Amawi,
Walaa AlKasasbeh,
Manar Jaradat
et al.

Abstract: Nutrition serves as the cornerstone of an athlete’s life, exerting a profound impact on their performance and overall well-being. To unlock their full potential, athletes must adhere to a well-balanced diet tailored to their specific nutritional needs. This approach not only enables them to achieve optimal performance levels but also facilitates efficient recovery and reduces the risk of injuries. In addition to maintaining a balanced diet, many athletes also embrace the use of nutritional supplements to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…The actual model of sports nutrition advocates regular intakes of simple carbohydrates, nutritional supplements, and proteins before and after exercise (here defined as 'Westernized athletic nutrition') to restore burning energy and structural protein synthesis [32]. Here, we…”
Section: Effects Of Nutrition On Metabolic Acidosis In High-intensity...mentioning
confidence: 99%
See 2 more Smart Citations
“…The actual model of sports nutrition advocates regular intakes of simple carbohydrates, nutritional supplements, and proteins before and after exercise (here defined as 'Westernized athletic nutrition') to restore burning energy and structural protein synthesis [32]. Here, we…”
Section: Effects Of Nutrition On Metabolic Acidosis In High-intensity...mentioning
confidence: 99%
“…The actual model of sports nutrition advocates regular intakes of simple carbohydrates, nutritional supplements, and proteins before and after exercise (here defined as ‘Westernized athletic nutrition’) to restore burning energy and structural protein synthesis [ 32 ]. Here, we would like to present an alternative viewpoint based on the premise that systemic health is before acute performance to stimulate the innate biological potential (see Figure 1 and Figure 2 ).…”
Section: Effects Of Nutrition On Metabolic Acidosis In High-intensity...mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the level of autonomy adolescent athletes possess over their diet and physical activities, having a grasp of nutrition can play a pivotal role in cultivating appropriate eating behaviors in this group. Nevertheless, research in diverse cultural settings has exposed gaps in athletes’ nutritional understanding, encompassing both general nutritional aspects ( 24 ) and comprehension of their sport-specific requirements ( 23 , 25 ). These knowledge deficiencies can be amplified by misconceptions about dietary practices ( 23 ) that may stem from superstitions or unreliable advice.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that tailored nutritional interventions positively impact performance outcomes [1,[4][5][6][7]. Personalized nutrition, driven by technological advancements and understanding individual differences, aims to provide tailored dietary recommendations based on an individual's unique characteristics and goals [8,9].…”
Section: Introductionmentioning
confidence: 99%